Integrated assessment of seed desiccation, storage, and viability of Grammatophyllum speciosum for ex-situ conservation - DWI MURTI PUSPITANINGTYAS; SURYA DIANTINA; RATNA YUNIATI; ELIZABETH HANDINI; POPI APRILIANTI; RETNO LESTARI (Society for Indonesian Biodiversity, 2026)
Abstract. Puspitaningtyas DM, Diantina S, Yuniati R, Handini E, Aprilianti P, Lestari R. 2026. Integrated assessment of seed desiccation, storage, and viability of Grammatophyllum speciosum for ex-situ conservation. Biodiversitas 27 (3): d270323. https://doi.org/10.13057/biodiv/d270323. Orchid seed banking is recognized as an efficient ex-situ conservation strategy. However, standardized protocols for seed drying, storage, and viability assessment are still lacking for many tropical species. This study evaluated the effects of desiccation duration, frozen storage at -20°C, and tetrazolium chloride (TTC) staining to develop a practical conservation protocol for Grammatophyllum speciosum. Fresh seeds were dried over silica gel for 3-9 days and germinated asymbiotically on several basal media. Seed viability after one year of storage was assessed using eight TTC pre-treatments that combined NaOCl scarification, sucrose pre-conditioning, and two TTC concentrations. Germination was significantly influenced by drying duration, and a significant interaction between medium and drying period was detected (ANOVA, p<0.01). The highest germination (74.82%±6.01) was obtained after three days of drying on Vacin & Went (VW) medium, whereas prolonged drying (6-9 days) reduced germination to 55-65%. After one year of storage at -20°C, seeds retained high viability (71.87-72.98%), with no significant decline compared to fresh seeds, indicating tolerance to both desiccation and subzero conditions. TTC-based viability assessment revealed significant differences among pre-treatments (ANOVA, p<0.001). Combined NaOCl scarification and sucrose pre-conditioning improved staining clarity, producing the highest viability values (up to 73.57%±5.16). No significant difference was observed between 0.1% and 1% TTC concentrations, demonstrating that the lower concentration was sufficient for reliable viability estimation. TTC-based viability closely matched germination results, indicating the consistency of direct and indirect assessment methods. Overall, short-term desiccation (3 days), storage at -20°C, and optimized TTC pre-treatment provide a scalable and resource-efficient strategy for orchid seed banking. This protocol supports the long-term preservation of genetic diversity and contributes to conservation management of threatened epiphytic orchids.